Method for improving pure aluminum cast-rolled grain structure
By replenishing titanium and online refining grains during the casting and rolling process, the problem of insufficient grain size and second phase structure uniformity of cast-rolled 1-type pure aluminum billet is solved, and the quality and performance of the finished aluminum foil is improved.
Patent Information
- Application Number
- CN202510103056.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art is difficult to effectively improve the grain size grade and the uniformity of the second phase structure of cast-rolled 1-type pure aluminum billets, resulting in the problems of color difference, many holes and unqualified performance of the finished aluminum foil.
By replenishing the aluminum-titanium alloy in the smelting furnace and adding aluminum-titanium boron wire before the inlet of the degassing chamber, the particle size of the aluminum-titanium boron wire and the front box liquid level height are controlled to refine the grains online and evenly distribute the second phase.
The grain size level of the cast-rolled plate is improved and the uniform distribution of the second phase structure is achieved, surface color difference, holes and performance defects are reduced, and the requirements of blanks for lithium batteries are met.
Smart Images

Figure CN119913383A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal aluminum material processing, and more specifically, to a method for improving the pure aluminum casting grain structure. Background Art
[0002] Series 1 pure aluminum is widely used in the production of aluminum plates, strips, and foils due to its high aluminum content, low strength, good hot and cold processing performance, high thermal conductivity, electrical conductivity, corrosion resistance, and excellent welding performance. In recent years, it has been widely used as the preferred series of battery aluminum foil products. Casting and rolling are also widely used in the production of aluminum plates, strips, and foils due to their simple equipment, short process, low investment, and low production cost. They are the mainstream production method in the aluminum foil industry. However, the disadvantages of casting and rolling are also very obvious. Its surface quality, internal organization, and processing performance are not as good as those of hot rolling, and it is difficult to meet the needs of high-end application fields of materials, such as battery aluminum foil products with high requirements for surface quality, finished product hole defects, and finished product performance.
[0003] With the requirements for improving the quality of battery aluminum foil, the quality of cast-rolled 1 series pure aluminum billets is becoming increasingly strict. Among them, the internal metallographic structure of cast-rolled 1 series pure aluminum has an important impact on the quality of the finished product. At present, the battery aluminum foil industry generally requires a lower grain size grade and a uniformly distributed second phase structure, so that the finished product has fewer surface color differences, holes and performance defects. However, due to the small number of nucleation points inside pure aluminum, coupled with the unreasonable equipment or production process in actual production, the grain size of the cast-rolled billet is too large and the second phase is unevenly distributed. Due to the coarse grains and uneven second phases of the cast-rolled billet, the probability of gas and slag inclusion inside the coarse grains is high, and it is not easy to escape from the cast-rolled plate. At the same time, large-sized second phases and foreign matter are easily gathered on the grain boundaries between the coarse grains, which ultimately leads to surface color differences, many holes and unqualified performance of the finished foil. Some companies adopt the method of increasing the amount of aluminum-titanium-boron wire added to increase the number of nucleation points, but this increases the risk of titanium slag inclusion and also increases production costs; some companies adopt the method of lowering the temperature of molten aluminum and improving the cooling intensity, but there is a risk of insufficient melting and the equipment requirements are also high.
[0004] The prior art discloses a method for preparing a cast-rolled strip that reduces the incidence of level-five grains in a 1060 aluminum alloy. The method smoothly controls the temperature control range of each link in smelting and online processing to avoid large temperature fluctuations, thereby controlling the occurrence of level-five grains in the casting and rolling process of the 1060 alloy. However, the grains of the obtained aluminum alloy only meet the level-five requirements, which is difficult to apply in the field of batteries requiring high precision. In addition, the second phase structure of the material is not further controlled, and the strength and toughness of the material are not further improved.
[0005] Therefore, a method for improving the grain structure of pure aluminum casting and rolling is developed, so that the grain size grade of the obtained aluminum plate is improved and the second phase structure is uniform, which has important application value. Summary of the invention
[0006] In order to overcome the above-mentioned deficiencies of the prior art, the primary purpose of the present invention is to provide a method for improving the grain structure of pure aluminum casting and rolling, so that the grain size grade of aluminum plates produced by the casting and rolling method is improved, the second phase structure is uniform, and the requirements for lithium battery billets are met.
[0007] Another object of the present invention is to provide a cast-rolled billet prepared by the above-mentioned improved method.
[0008] Another object of the present invention is to provide an application of the above-mentioned cast and rolled billet.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] The present invention provides a method for improving the grain structure of pure aluminum casting, comprising the following steps:
[0011] S1. Add titanium before the furnace; add aluminum-titanium alloy in the smelting furnace;
[0012] S2. Online grain refinement: AlTi 5 B 1 Add before the degassing chamber entrance;
[0013] S3. The liquid level of the front tank is controlled at 13-20 mm;
[0014] Wherein, the titanium content in the aluminum melt after the titanium supplementation in front of the furnace is 0.008-0.015%;
[0015] The aluminum titanium boron wire AlTi 5 B 1 The addition amount is 1-2 kg / ton of aluminum water;
[0016] The aluminum titanium boron wire AlTi 5 B 1 Any 1cm 2 TiB in the longitudinal section 2 The average particle size of TiAl is less than 2μm. 3 The average particle size is less than 30 μm, and the casting and rolling machine used is an inclined casting and rolling machine.
[0017] The process of producing pure aluminum by casting and rolling is to first feed materials (including pure aluminum ingots or waste materials or aluminum liquid) into the smelting furnace, adjust the composition after melting, refine the melt and remove the slag, and finally pour all the aluminum liquid into the insulation furnace / static furnace below after the composition and temperature reach the target, and then refine and remove the slag and take samples to determine the composition in the insulation / static furnace, and then the aluminum liquid flows into the degassing chamber through the flow trough for online degassing (reducing the hydrogen content in the aluminum liquid). The present invention adopts the online grain refinement method for AlTi 5 B 1The titanium wire is added to the flow channel before the degassing chamber entrance, and the degassing rotor in the degassing chamber moves to refine the grains of TiB in the titanium wire. 2 / TiAl 3 After being fully dispersed and evenly distributed, the aluminum liquid then flows to the filter box (filter plate / filter tube) for online filtration to remove large-sized foreign matter. After filtration, the aluminum liquid flows to the front box through a section of active flow trough. The temperature / liquid level difference height of the front box has an important influence on the grain size of the cast-rolled plate. The aluminum liquid behind the front box is diverted through the casting nozzle and cooled by the casting and rolling rollers above and below the casting nozzle (with cooling water inside) to form the aluminum plate. The continuously produced aluminum plates are produced through a shearing machine (which can be cut) and a final coiler to produce rolls of qualified cast-rolled coils.
[0018] The present invention adds a certain amount of aluminum-titanium alloy containing aluminum and titanium elements when feeding the smelting furnace. The prior art only adds aluminum-titanium-boron wire before degassing. Due to the difference in the temperature of the titanium wire addition point, the requirements for the addition speed and the degassing filtering equipment, the actual grain refining material TiB in the aluminum-titanium-boron wire is 2 / TiAl 3 Absorption rate fluctuates greatly. When it is unreasonable or abnormal, it is very easy to cause low content and uneven distribution of titanium compounds in the aluminum liquid at the front box, which eventually leads to abnormal structure of the cast plate. However, the present invention innovatively adds aluminum-titanium alloy to the melting furnace, so that there is a certain content of Ti and TiAl in the melt before adding aluminum-titanium-boron wire. 3 The original grain structure is also smaller than that of adding aluminum titanium boron wire only before degassing, so after adding titanium wire, not only the nucleation points are further increased, but also the composition of the finished product is more uniform and the performance consistency of the finished product is better. The present invention requires that the titanium content in the aluminum melt after the furnace is supplemented with titanium is within a certain range, because if the titanium content before the furnace is too low, the introduced TiAl 3 The fewer the refined particles, the weaker the effect of suppressing the coarsening of grains in the melt. On the contrary, too high titanium content before the furnace will cause titanium compounds to aggregate and grow in the melting furnace and the holding furnace to form foreign matter slag or deposit on the lower surface of the cast and rolled plate to form white strip color defects in the thin product, and will also cause the titanium content after the furnace to exceed the standard.
[0019] In the step of online grain refinement of the present invention, the particle size of the aluminum titanium boron wire needs to be controlled, and the aluminum titanium boron wire AlTi 5 B 1 Any 1cm 2 TiB in the longitudinal section 2 The average particle size of TiAl is less than 2μm. 3 The average particle size is less than 30μm. The more particles there are, the less foreign matter and impurities there are, so that more high-quality nucleation particles can be added to the aluminum melt. At the same time, TiB 2 / TiAl 3 The probability of titanium compounds being intercepted and deposited is lower, and fewer impurities and foreign bodies are introduced into the melt.5 B 1 The amount of addition is within a certain range, because if the amount added is too large, on the one hand, it is easy to cause insufficient dissolution and absorption of effective refined particles, and more invalid titanium compounds will remain in the box, causing waste; on the other hand, too many titanium compounds will easily aggregate and grow in the aluminum liquid to form foreign matter slag or deposit on the lower surface of the cast-rolled plate to form white stripe color difference defects in the thin product; if the amount added is small, the number of refined particles will be small, which can easily cause uneven coarse grains and second phase structure of the cast-rolled plate level 5.
[0020] By controlling the liquid level of the front box during casting and rolling (the height difference between the liquid level of the front box and the front edge of the casting nozzle opening), the normal supply of aluminum liquid is guaranteed, so that the casting and rolling process can proceed normally, and at the same time, the possibility of slag inclusion in the cast-rolled plate caused by the oxide film at the curved liquid surface being easily broken due to the excessively high liquid level of the front box is avoided; in addition, when the liquid level of casting and rolling is too low, the tiny nucleation particles, including their own and foreign TiB 2 Nucleation particles, due to their high density, produce gravity segregation, which leads to serious titanium deposition on the lower plate surface during casting and rolling, "white stripes" or color difference defects in subsequent rolling, and the upper plate surface has a reduced titanium content, which weakens the refining ability, resulting in "patterned plates" or five-level coarse grains, especially for pure aluminum with few nucleation particles. In the liquid level height range defined by the present invention, the difference in crystal structure of the upper and lower cast-rolled plate surfaces and the uniformity of the second phase distribution due to the inclined casting and rolling method can be significantly improved. The potential energy of the aluminum liquid increases, and the kinetic energy will also increase accordingly. The uniformity and dispersion of the nucleation particles are improved due to diffusion, which can significantly improve the difference in crystal structure of the upper and lower cast-rolled plate surfaces and the uniformity of the second phase distribution due to the inclined casting and rolling method.
[0021] The inclined casting and rolling mill is selected according to the existing technology, and the inclined casting and rolling mill used in the industry is a 15° inclined twin-roll casting and rolling mill.
[0022] Preferably, the aluminum-titanium alloy is an aluminum-titanium rod AlTi 6 A.
[0023] Preferred aluminum titanium rod AlTi 6 A, it is compatible with aluminum melt quickly, fully absorbed, high grade, and contains few foreign impurities.
[0024] Preferably, the titanium content after the pre-furnace titanium supplementation is 0.018-0.012%.
[0025] Specifically, the titanium content in the aluminum melt, that is, the titanium content after titanium supplementation before the furnace, is chemically detected and determined by a direct-reading spectrometer.
[0026] Preferably, the aluminum titanium boron wire AlTi 5 B 1 The amount of addition is 1.5 to 2 kg per ton of aluminum water.
[0027] Preferably, the aluminum titanium boron wire AlTi 5 B 1 Request TiB 2 Any 1cm 2 TiB in the longitudinal section 2 The average particle size is <2μm, and the distribution is roughly uniform and dispersed. TiB with a size of <25μm is allowed. 2 Loose clumps, no more than 3; requires TiAl 3 Any 1cm 2 TiAl in the longitudinal section 3 In block or rod shape, roughly evenly distributed, the average particle size is <30μm, and the maximum size of a single particle is <125μm. The above parameters are determined by metallographic examination.
[0028] Refer to national standard YS / T447.1-2011, alloy wire for grain refinement of aluminum and aluminum alloys, industry grade A.
[0029] Preferably, the liquid level in the front box is 15-18 mm.
[0030] In the art, the front box liquid level is defined as the height difference between the liquid level in the front box and the middle position of the thickness of the front edge of the casting nozzle outlet. It can be measured by referring to the method known in the prior art, and can be measured with a measuring device, such as the measuring device described in CN218916463U.
[0031] The aluminum liquid temperature of the front box is selected with reference to the prior art.
[0032] Preferably, the aluminum liquid temperature of the front box is 695±5°C, and more preferably 695±3°C.
[0033] Preferably, the method for improving the pure aluminum casting grain structure further comprises the following steps:
[0034] Pure aluminum ingots or scrap or aluminum liquid are added to the smelting furnace for melting, the melt is refined and slag is removed, the holding furnace / static furnace is refined and slag is removed, online degassing is carried out, the aluminum liquid is filtered by the filter box, the casting and rolling mill and the casting and rolling rolls are processed, cooled and formed, and the shearing machine produces billets.
[0035] Specifically, the method for improving the pure aluminum casting grain structure further includes the following steps:
[0036] S1. Melting furnace: put the pure aluminum ingot into the melting furnace and ignite and heat it. After it is flattened, argon gas is purged and electromagnetic stirring is performed during the process. When the aluminum liquid reaches 740±5℃, the content of Si, Fe and Cu elements is measured and AlTi is added after it meets the use requirements. 6A rod operation, fast addition, then use argon + refining agent for refining, slag removal after refining, the temperature of aluminum liquid decreases after refining, and the aluminum liquid temperature needs to be further raised to 750-760℃ and then the furnace is poured according to the situation of the holding furnace;
[0037] S2. Holding furnace / static furnace: The holding furnace is a tilting type. When the temperature of the melting furnace is qualified and the aluminum liquid is poured into the furnace and drops to the lowest position, pure argon gas refining is carried out in the holding furnace to maintain the temperature of the aluminum liquid in the holding furnace, and a static sample is taken to confirm the composition. There is an infrared liquid level position detection device at the outlet of the holding furnace, which can adjust the lifting speed of the holding furnace according to the feedback of the liquid level position change. It is necessary to ensure that the fluctuation amplitude of the outlet liquid level is less than or equal to 5mm to reduce the impact on stable production;
[0038] S3. Degassing box: The aluminum liquid in the holding furnace flows to the degassing box through a fixed flow channel. The entrance of the degassing box is aluminum titanium boron wire AlTi 5 B 1 At the adding point, the aluminum titanium boron wire is carried into the aluminum water by the feeding equipment and then passes through the heating and swinging device, which can improve the dissolution and release of effective substances in the aluminum titanium boron wire, and avoid the aluminum titanium boron wire from being insufficiently dissolved and deposited at the bottom. The degassing chamber adopts the argon double rotor mode for online degassing, which improves efficiency and reduces failure losses. The material used is silicon nitride rotor, the rotor speed is 550r / min, the argon pressure is 0.8MPa, and the argon flow rate is 15L / min, which ensures that the number of bubbles is large and the single diameter is small. The aluminum liquid temperature in the degassing chamber is controlled at 720±5℃;
[0039] S4. Filter box: Use double-stage filter plates, and the aluminum liquid temperature in the filter box is controlled at 710-720℃;
[0040] S5. Front box: The liquid level of the front box is controlled at 15-18 mm, and the temperature of the front box is controlled at 695±5℃;
[0041] S6. Casting and rolling: The aluminum liquid in the front box is diverted through the casting nozzle and passed through the inclined casting and rolling mill and rollers to produce cast-rolled plates with a width slightly wider than the casting nozzle. The cast-rolled plates can be cut into coils online after passing through the plate cutting machine. Qualified cast-rolled plates are finally coiled by the reverse coiler into cast-rolled coil blanks with an inner diameter of 610mm and an outer diameter that meet the requirements of customers and cold rolling mills. A full-width plate sample with a length of 200-300mm is cut from the end of each coil for inspection of low-magnification grain size, high-magnification metallographic structure and second phase.
[0042] Preferably, the thickness of the cast plate is 6.0-7.0 mm.
[0043] Preferably, the linear speed requirement of the casting roll is 800-1100 mm / min, more preferably 900-1000 mm / min.
[0044] Preferably, the diameter of the casting roll is 800-900 mm.
[0045] Preferably, the refining agent is an environmentally friendly refining agent, and is not a self-heating type containing fluorine elements. More preferably, it is a Pyrotech granular refining agent.
[0046] Preferably, the blank produced by the present invention is a cast-rolled pure aluminum alloy blank for lithium batteries, with a thickness of 6 to 7 mm. The chemical composition of the blank satisfies the following mass percentage composition: Al residue ≥ 99.00%, especially suitable for Al residue of 99.60 to 99.90%.
[0047] The present invention also protects a casting and rolling billet prepared by the above improved method.
[0048] The use of the above-mentioned cast-rolled billet in the preparation of lithium battery aluminum foil is also within the protection scope of the present invention.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] The present invention provides a method for improving the grain structure of pure aluminum casting, which can obtain a lower grain size grade and a uniformly distributed second phase structure. By adding an appropriate amount of titanium to the smelting furnace, controlling the particle size of the aluminum titanium boron wire, and increasing the liquid level of the front box, the present invention not only reduces the difference in grain size between the upper and lower casting plates, but also improves the quality of the finished product, reduces surface color difference, holes and performance defects. In addition, the method of the present invention has low production cost, high efficiency, and good practicality, which helps to improve the market competitiveness of products in high-end application fields such as battery aluminum foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] the following Figures 1 to 8 All images are taken with a metallographic microscope, OLYMPUS, Japan.
[0052] Figure 1 : Comparative Example 3 Aluminum Titanium Boron Silk Point Size Arbitrary 1cm 2 TiB in the longitudinal section 2 / TiAl 3 When the average particle size is more than 2 / 30, the size of the second phase is coarse and uneven;
[0053] Figure 2 : Comparative Example 1 The particle size of aluminum titanium boron silk is any 1cm 2 TiB in the longitudinal section 2 / TiAl 3 The average particle size is less than 2 / 30 of the second phase, which is small and uniform;
[0054] Figure 3 : Comparative Example 7 Coarse grains on the upper surface of the cast-rolled billet;
[0055] Figure 4 : Comparative Example 7 Coarse grains on the lower surface of the cast billet;
[0056] Figure 5 : Fine grains on the upper surface of the cast-rolled billet of Example 1;
[0057] Figure 6 : Fine grains on the lower surface of the cast-rolled billet in Example 1;
[0058] Figure 7 : Comparative Example 2 The thickness of the cast billet is uneven in the middle of the second phase;
[0059] Figure 8 : Example 1 The second phase is uniform in the middle of the thickness of the cast and rolled billet. DETAILED DESCRIPTION
[0060] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0061] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0062] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0063] Casting and rolling raw materials: The aluminum ingots used are Al 99.85 aluminum ingots produced by Guangxi Laibin Guangtou Yinhai Aluminum Co., Ltd. The production process uses hydropower clean energy to ensure that the aluminum ingot production process is green and environmentally friendly. The aluminum content of pure aluminum ingots is greater than or equal to 99.85% to ensure that there are few foreign bodies and slag inclusions inside. Aluminum ingots with Cr, V, and Ga content less than 50ppm are selected.
[0064] Aluminum titanium boron wire grade: passed metallographic inspection.
[0065] Titanium content after titanium supplementation before furnace: detected by direct reading spectrometer.
[0066] The methods of various embodiments and comparative examples of the present invention are as follows:
[0067] S1. Melting furnace: put the pure aluminum ingot into the melting furnace and ignite and heat it. After it is flattened, argon gas is purged. During this period, electromagnetic stirring is performed 3 times, each stirring time is 15 minutes. When the aluminum liquid reaches 740℃, the Si, Fe, and Cu element contents are measured and AlTi is added after they meet the use requirements. 6 A rod operation, rapid addition, so that the Ti content in the aluminum melt is 0.008-0.015%, after 60 minutes, argon + Pyrotech granular refining agent is used for refining, the refining agent usage is 1.5Kg / ton aluminum water, the refining time is 30 minutes, after refining, slag is removed, after refining, the aluminum water temperature drops, and the aluminum liquid temperature needs to be further raised to 755℃ and then the furnace is poured according to the situation of the holding furnace;
[0068] S2. Holding furnace / static furnace: The holding furnace is a tilting type. When the temperature of the melting furnace is qualified and the aluminum liquid is poured into the furnace and drops to the lowest position, pure argon gas refining is carried out in the holding furnace. The refining time is 25 minutes. The aluminum liquid temperature of the holding furnace is maintained at 745℃, and static samples are taken to confirm the composition. There is an infrared liquid level position detection device at the outlet of the holding furnace, which can adjust the lifting speed of the holding furnace according to the feedback of the liquid level position change. It is necessary to ensure that the fluctuation amplitude of the outlet liquid level is less than or equal to 5mm to reduce the impact on stable production;
[0069] S3. Degassing box: The aluminum liquid in the holding furnace flows to the degassing box through a fixed flow channel. The entrance of the degassing box is aluminum titanium boron wire AlTi 5 B 1 At the adding point, the aluminum titanium boron wire is carried into the aluminum water by the feeding equipment and then passes through the heating and swinging device, which can improve the dissolution and release of effective substances in the aluminum titanium boron wire and avoid the aluminum titanium boron wire from being insufficiently dissolved and deposited at the bottom. The adding amount is 1.5kg / ton of aluminum water. The degassing chamber adopts the argon double rotor mode for online degassing to improve efficiency and reduce failure losses. The material used is silicon nitride rotor, the rotor speed used is 550r / min, the argon pressure used is 0.8MPa, and the argon flow rate is 15L / min, which ensures that the number of bubbles is large and the single diameter is small. The aluminum liquid temperature in the degassing chamber is controlled at 720±5℃;
[0070] S4. Filter box: Use 50+60PPI double-stage filter plate, Pyrotech product, and the aluminum liquid temperature in the filter box is controlled at 710-720℃;
[0071] S5. Front box: control the liquid level of the front box and the temperature of the front box at 695±5℃;
[0072] S6. Casting and rolling: The aluminum liquid in the front box is diverted through the casting nozzle and passes through a 15° inclined two-roller rolling mill with a roller diameter of 850mm to produce a cast-rolled plate with a thickness of 6.5mm and a width slightly wider than the casting nozzle. The roller line speed is controlled at 950mm / min. The cast-rolled plate can be cut into coils online after passing through a plate cutter. Qualified cast-rolled plates are finally coiled by a reverse coiler into cast-rolled coil blanks with an inner diameter of 610mm and an outer diameter that meet the requirements of customers and cold rolling mills. A full-width plate sample with a length of 250mm is cut from the end of each coil for inspection of low-magnification grain size, high-magnification metallographic structure and second phase.
[0073] The performance testing methods and standards of the billets obtained by casting and rolling in the embodiments of the present invention and the comparative examples are as follows:
[0074] (1) Grain size grade of cast and rolled billet: evaluated in accordance with clause 4.3.2 of GB / T 3246.2-2012 “Microstructure test methods for wrought aluminum and aluminum alloy products Part 2: Macrostructure test methods”;
[0075] (2) The uniformity of the second phase in the middle of the cast billet thickness; under 500x optical microscope observation, if the second phase shows obvious blank and black groove differences, it means poor uniformity, whereas if there is no obvious blank area or black groove area, it means good uniformity;
[0076] (3) Finished product hole grade: divided into poor, good, and excellent; the total number of holes is less than 1000, and large holes (area ≥ 0.1mm 2 ) number < 20 is excellent; the total number of holes < 5000, large holes (area ≥ 0.1mm 2 ) number <100 is good; the total number of holes >5000, large holes (area ≥0.1mm 2 ) The number is less than 20, which is considered poor;
[0077] (4) Finished product surface quality: normal / white stripe color difference, where white stripes are the phenomenon that the surface of the aluminum foil appears bright white in stripes, which is different from the silvery white surface of ordinary aluminum foil. It is an appearance defect that affects customer acceptance and use.
[0078] The experimental conditions of the embodiments / comparative examples of the present invention are shown in Table 1.
[0079] Table 1 Casting and rolling experimental conditions of the embodiments and comparative examples
[0080]
[0081]
[0082] The experimental results of the embodiments / comparative examples of the present invention are shown in Table 2.
[0083] Table 2 Test results of cast and rolled billets of embodiments and comparative examples
[0084]
[0085] The improved conditions of the pure aluminum casting grain structure of Examples 1 to 8 obtained the cast-rolled billets with improved grain size and uniform second phase structure, meeting the requirements for billets for lithium batteries.
[0086] In comparative example 1, the titanium content after titanium supplementation in the smelting furnace is too much and exceeds the range, resulting in a large amount of residual titanium compounds in various places in the smelting furnace and the holding furnace, which is very easy to form large particles of foreign matter slag, which is inherited into the cast and rolled plate. The final product has a high porosity and a relatively low porosity grade. In addition, the Ti element content after the furnace is not well controlled, and it exceeds the standard frequently, which does not meet the production requirements.
[0087] In comparative example 2, the titanium content in the smelting furnace is too low after titanium is added, and the TiAl3 refined particles in the smelting furnace and the holding furnace are very few, which makes it difficult to effectively play the role of inhibiting the premature growth of grains. The grain grade of the cast-rolled plate is high, and the uniformity of the second phase in the thickness of the cast-rolled plate is relatively poor. Ultimately, the purpose of improving the structure of the cast-rolled plate cannot be achieved, and the porosity grade is relatively low.
[0088] Comparative Example 3 is to select any 1cm of aluminum titanium boron wire 2 TiB in the longitudinal section 2 The average particle size of TiAl is less than 2μm. 3 The average particle size of TiB is above 30μm. 2 The average particle size of TiAl is 1.86. 3 The average particle size is 40.5, the grain refining substances TiAl3 and TiB2 are larger in size and less in number, and contain more foreign matter and impurities, which not only weakens the grain refining effect but also increases the risk of slag inclusion. The quality of the cast and rolled coils and the finished products cannot reach level 1.
[0089] In comparative example 4, the liquid level of the front box is low, the kinetic energy of the aluminum liquid casting nozzle is low, the contact between the aluminum liquid and the upper and lower rollers is lower, the cooling effect is worse, the grains are coarser, especially the upper surface of the cast plate is more likely to have coarse grains, and at the same time, the effective nucleation particles (mainly titanium compounds) inside the aluminum liquid sink due to insufficient kinetic energy and gravity, which further aggravates the difference in the organization of the upper and lower plate surfaces, and the overall grain size is coarse and the second phase is uneven. The probability of gas and slag inside the cast plate is high, and the finished product has poor holes;
[0090] Comparative Example 5: The higher the liquid level in the front box, the greater the pressure on the front curved liquid surface at the outlet of the casting nozzle, and the higher the probability of the oxide film rupture at the curved liquid surface, which can easily lead to slag inclusion in the cast plate and poor hole quality in the finished product;
[0091] In Comparative Example 6, the amount of aluminum-titanium-boron wire added is too much, exceeding the range. Due to the difference in adding conditions, the probability of insufficient dissolution and absorption is high, and titanium compounds are easily left in each box and flow channel. A large number of titanium compounds gather and grow and inherit to the cast and rolled plate to form slag inclusions. A large number of titanium compounds appear in the lower surface area of the cast and rolled plate, showing white strip color difference defects during thinning.
[0092] In Comparative Example 7, too little aluminum-titanium-boron wire is added, so the amount of effective refining material is small, and the effect of online grain refinement is not achieved. The grain size grade is 5, the thickness of the second phase is obviously uneven, the probability of internal gas and slag is high, the finished product hole grade is poor, and the finished product surface reflectivity is low.
[0093] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for improving the grain structure of pure aluminum casting, characterized in that: The following steps are involved: S1. Add titanium before the furnace; add aluminum-titanium alloy in the smelting furnace; S2. Online grain refinement: Add aluminum titanium boron wire AlTi5B1 before the degassing chamber entrance; S3. The liquid level of the front tank is controlled at 13-20 mm; Wherein, the titanium content in the aluminum melt after the titanium supplementation in front of the furnace is 0.008-0.015%; The amount of AlTi5B1 added is 1-2 kg / ton of aluminum liquid; Any 1cm of the aluminum titanium boron wire AlTi5B1 2 In the longitudinal section, the average particle size of TiB2 is less than 2 μm, and the average particle size of TiAl3 is less than 30 μm. The casting and rolling machine used is an inclined casting and rolling machine.
2. The method according to claim 1, characterized in that The titanium content in the aluminum melt after the titanium addition in the furnace in step S1 is 0.010-0.012%.
3. The method according to claim 1, characterized in that Any 1cm of TiB2 in the aluminum titanium boron wire AlTi5B1 2 The average size of TiB2 particles in the longitudinal section is less than 2μm, and the distribution is roughly uniform. Loose TiB2 agglomerates with a size of less than 25μm are allowed, and no more than 3; any 1cm TiAl3 2 In the longitudinal section, TiAl3 is blocky or rod-shaped and distributed roughly evenly. The average size of the particles is <30μm, and the maximum size of a single particle is <125μm.
4. The method according to claim 1, characterized in that In the step S2, the amount of aluminum titanium boron wire AlTi5B1 added is 1.5-2 kg / ton of aluminum liquid.
5. The method according to claim 1, characterized in that In step S3, the liquid level in the front box is 15-18 mm.
6. The method according to claim 1, characterized in that The aluminum liquid temperature of the front box in step S3 is 690-700°C.
7. The method according to claim 1, characterized in that The method for improving the grain structure of pure aluminum casting and rolling also includes the following steps: adding pure aluminum ingots or waste materials or aluminum water into a smelting furnace for melting, refining and slagging the melt, refining and slagging the melt in a holding furnace / stationary furnace, online degassing, filtering the aluminum liquid in a filter box, treating a casting and rolling mill and casting and rolling rolls, cooling and forming, and producing billets with a shearing machine.
8. The method according to claim 7, characterized in that The linear speed requirement of the casting and rolling roll is 800-1100 mm / min.
9. A cast-rolled billet, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the cast-rolled billet according to claim 9 in the preparation of lithium battery aluminum foil.
Citation Information
Patent Citations
Device for measuring liquid level height of front box of casting and rolling machine
CN218916463U
Cited By
High-purity aluminum foil grain refinement method adopting cubic orientation segregation method
CN121023268A
A combined process for adding, homogenizing, and refining aluminum-titanium-boron wires
CN122665957A